Młodzież a przystosowanie się do otoczenia = Adolescents and the process of adapting to the environment - Olszak-Krzyżanowska, Bożena (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This work is concerned with the complicated process of building young people`s relations with the surrounding world. Analyzing this process, I tried to show possibly many factors influencing adolescents` assimilation and adaptation processes in relation to the living space. These include personality, identity, and orientation. I also present the constructed typology of people who are focused on themselves as well as those who are concentrated on and oriented towards others. During the process of constructing this typology, I took into account the type of personalities, interactions, relations to social norms, life orientation, and the feeling of identity.
Keywords: młodzież; przystosowanie; osobowość; tożsamość; rozwój człowieka